Access to Primary Care and Preventative Health Services of Migrants (SpringerBriefs in Public Health,, 2018)
This salient volume surveys the state of access to primary care and preventive health services by migrants, refugees, and asylum seekers across Europe. Experts in public health and allied fields identify obstacles to healthcare interventions for migrants, including costs, legal status, health-related behaviors and beliefs, and cultural and language barriers. The book includes the latest data concerning access to specific preventive services (e.g., vaccinations, colorectal screenings), specific issues of women and sexual minorities, and the potential for health promotion in prevention. Best practices for improving access are outlined as a basis for public health and policy directives toward reducing health disparities between migrant and native populations. Among the topics covered: Access to medical examination for prevention among migrants Access and barriers to infant vaccinations, female cancer screening and colorectal screening among migrant populations Provision and policy gap between the primary and preventive care required by and the care provided to LGBTQ+ migrants, refugees, and asylum seekers. Health related lifestyles and intermediate health conditions of migrants. Quality of primary healthcare and preventive health services provided to migrants Adaptations of primary health care for migrants Access to primary health care and policies on migration and health at a time of economic crisis Dedicated to bridging research and policy gaps in this vital area, Primary Care Access and Preventive Health Services of Migrants is intended for an international audience of academics, researchers, policymakers, and practitioners in public health and related disciplines.